Towards net zero land biotechnology: an assessment of biogenic feedstock potential for selected bioprocesses in Germany - Adrian Tüllinghoff; Heike Sträuber; Flávio Cesár Freire Baleeiro; Andreas Aurich; Micjel Chávez Morejón; Kathleen Meisel; Karl-Friedrich Cyffka; Falk Harnisch; Katja Bühler; Daniela Thrän (Biotechnology for Biofuels and Bioproducts)
Abstract To stay within the planetary boundaries circularizing economy by utilizing residues is key. Bioprocesses can use abundant, but complex biogenic residues, giving access to various value-added products. To advance circularization, the feasibility of exploiting diverse biogenic residues as feedstocks for different, yet specific, bioprocesses needs to be assessed. Exemplifying the national level in Germany, we categorized biogenic residues compiled in the DE Biomass Monitor regarding their composition and feedstock potential in a resource matrix, detailing their constituents and the quality of available data. Three biotechnological processes, making use of lignin, non-fibrous carbohydrates, and oil, respectively, served as model processes to assess the biogenic production potential. By developing material flows based on state-of-the-art conversion routes, we found that residue-based production via all three example processes could meet national demands of specific polymer bricks, medium chain carboxylates, and platform chemicals, respectively, when mobilizing only 20–30% of possible raw materials. The accruing side streams underline the importance of cluster approaches early in bioprocess development. Specific challenges for fully exploiting the potential of biogenic residues were identified, including legal and acceptance issues, the need for considered biomass decomposition in interweaved production lines, and residue availability and management. This study provides an example-based framework for integrating biogenic residues with biotechnological production, using the resource matrix and an initial material-to-product estimation to advance a circular bioeconomy.